2020
DOI: 10.1002/pbc.28229
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences in end‐of‐life decision‐making in allogeneic pediatric stem cell transplantation

Abstract: Background In pediatric hematopoietic stem cell transplantation (HSCT), the end‐of‐life (EOL) phase and the loss of the child is often characterized by a sudden deterioration of the child following a period of intensive curative treatment. This demands a fast transition for parents. Therefore, an understanding of the parents’ perspective on decision‐making in such a complex situation is needed. This study aims to gain insight in parental experiences in EOL decision‐making in allogeneic pediatric HSCT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…However, when clinicians offered emotional support and human social interaction, these relationships had a lasting and meaningful impact on the parent (West et al, 2020). Similarly, healthcare providers were integral in offering advice and maintaining hope for a cure, which enabled parents to continue caring for the child's needs and focus on the future (Mekelenkamp et al, 2020). Open discussion and joint decision making between the parent and provider are associated with PTG among parents of children with cancer (Wilson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, when clinicians offered emotional support and human social interaction, these relationships had a lasting and meaningful impact on the parent (West et al, 2020). Similarly, healthcare providers were integral in offering advice and maintaining hope for a cure, which enabled parents to continue caring for the child's needs and focus on the future (Mekelenkamp et al, 2020). Open discussion and joint decision making between the parent and provider are associated with PTG among parents of children with cancer (Wilson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study noted that the child's condition can deteriorate fast while the treatment is still focused on survival, resulting in less time to prepare for EOL [8]. Parent reports showed that, in hindsight, parents experienced concerns regarding their child's suffering [17] and were at greater risk of decreased psychological wellbeing [18,19]. In contrast, studies have shown that transplanted children, adolescents, and young adults who received (pediatric) palliative care were more likely to die outside the (P)ICU; this reflects an impact of palliative care involvement on a patient's location of death [4,6].…”
Section: Introductionmentioning
confidence: 86%
“…In case you do not take the opportunity, you will have remorse." 5 Together, these two articles demonstrate the tensions and conflicts parents experience as they navigate their child's end of life. Furthermore, these studies reinforce the importance of effective communication for parents during these difficult times.…”
mentioning
confidence: 99%
“…The second article in recent issues by Mekelenkamp and colleagues 5 provides further insights into the experiences of bereaved parents. These authors performed a qualitative interview study with parents of eight children who died after receiving a hematopoietic stem cell transplant.…”
mentioning
confidence: 99%
See 1 more Smart Citation